Van der Waals forces in density functional theory: a review of the vdW-DF method. (15th May 2015) - Berland, Kristian; Cooper, Valentino R; Lee, Kyuho; Schröder, Elsebeth; Thonhauser, T; Hyldgaard, Per; Lundqvist, Bengt I
Abstract: A density functional theory (DFT) that accounts for van der Waals (vdW) interactions in condensed matter, materials physics, chemistry, and biology is reviewed. The insights that led to the construction of the Rutgers–Chalmers van der Waals density functional (vdW-DF) are presented with the aim of giving a historical perspective, while also emphasizing more recent efforts which have sought to improve its accuracy. In addition to technical details, we discuss a range of recent applications that illustrate the necessity of including dispersion interactions in DFT. This review highlights the value of the vdW-DF method as a general-purpose method, not only for dispersion bound systems, but also in densely packed systems where these types of interactions are traditionally thought to be negligible.